Emergency braking is affected by the use of cruise control. (18th August 2017) - Jammes, Yves; Behr, Michel; Llari, Maxime; Bonicel, Sarah; Weber, Jean Paul; Berdah, Stephane
ABSTRACT: Objective : We compared the differences in the braking response to vehicle collision between an active human emergency braking (control condition) and cruise control (CC) or adaptive cruise control (ACC). Methods : In 11 male subjects, age 22 to 67 years, we measured the active emergency braking response during manual driving using the accelerator pedal (control condition) or in condition mimicking CC or ACC. In both conditions, we measured the brake reaction time (BRT), delay to produce the peak braking force (PBD), total emergency braking response (BRT + PBD), and peak braking force (PBF). Electromyograms of leg and thigh muscles were recorded during braking. The tonic vibratory response (TVR), Hoffman reflex (HR), and M-waves were recorded in leg muscles to explore the change in sensorimotor control. Results : No difference in PBF, TVR amplitude, HR latency, and H max / M max ratio were found between the control and CC/ACC conditions. On the other hand, BRT and PBD were significantly lengthened in the CC/ACC condition (240 ± 13 ms and 704 ± 70 ms, respectively) compared to control (183 ± 7 ms and 568 ± 36 ms, respectively). BRT increased with the age of participants and the driving experience shortened PBD and increased PBF. Conclusions : In male subjects, driving in a CC/ACC condition significantly delays the active emergency braking response to vehicle collision. This could result from higher amplitude of leg motion in the CC/ACC condition and/or by the age-related changes in motor control. Car and truck drivers must take account of the significant increase in the braking distance in a CC/ACC condition.